Investigation On Dielectric And Sound Absorption Properties Of Banana Fibers Reinforced Epoxy Composites - Elammaran, Jayamani; Sinin, Hamdan; Pushparaj, Ezhumalai; Muhammad Khusairy, Bin Bakri (UTM Press, 2016)
This research work focused on the development of banana fiber reinforced epoxy resin composites for dielectric and sound absorption applications. The dielectric and sound absorption properties of the composites were studied with respect to the fiber loading and treatment. The fibers were treated using 5wt % of sodium hydroxide at room temperature. The properties of the composites were measured using HP Impedance Analyzer E4980A and two-microphone transfer function impedance tube method according to the American Society for Testing Materials (ASTM D150-11 and ASTM E1050-12) standards. In general, the composites displayed higher dielectric constant and sound absorption coefficients at the higher fiber loading. In extend, the treated fibers reinforced composites showed higher sound absorption coefficients, but lower dielectric constant values.